SIMULASI SNORT SEBAGAI ALAT PENDETEKSI INTRUSI PADA WEB DAMN VULNERABLE WEB APPLICATION - Siti Madinah Ladjamuddin; I Gede Walid Bangga (JURNAL REKAYASA INFORMASI, 2022)
ABSTRACT On the Web Server object, the most influential factor is the stability and validity of the data. This is due to the variety of users accessing the Web server, so that it makes difficult to secure the Web server when it is available to the public. One way of securing it is to use an Intrusion Detection System in order to minimize the impact caused by the failure of a Web server caused by existing security holes. The application of Snort-Based Intrusion Detection System is a security system that is quite inexpensive but reliable in detecting attacks. The IDS system can also be implemented on the Windows operating system. On the IDS system attacks, it can be detected or not by Snort IDS Depending on the presence or absence of rules created by the user. Therefore, the purpose of this research is to design and build a Web server security system to monitor the network in real-time. To achieve this, the author uses Command Prompt as a medium to provide alerts if there is an attack and Snort as an Intrusion Detection System (IDS) tool. Testing the IDS system was carried out with several attack scenarios to test the quality of Snort in detecting attacks on the quality of the security system of a Web server. Based on the results of testing the Snort IDS system with ping, XSS Script, and SQL Injection, Snort can provide security attack warnings on Web server systems. The warning results can be used as a reference to determine network securitypolicies. Keywords : Security web, web server, intrution detection system, snort